Elucidating prognostic significance of purine metabolism in colorectal cancer through integrating data from transcriptomic, immunohistochemical, and single‐cell RNA sequencing analysis - Sungyeon Kim; Myunghee Kang; Soyeon Jeong; Jisup Kim; Kyoung Oh Kim; Won‐Suk Lee; Jeong‐Heum Baek; Jung Ho Kim; Seungyoon Nam (Molecular Oncology)
Colorectal cancer (CRC) is widely recognized for its high prevalence and significant mortality rates, and purine metabolism has been serving as a potential therapeutic target. However, purine metabolism has not yet been validated as a prognostic marker through immunohistochemical analysis. In this study, we utilized a combination of bulk transcriptome analysis, immunohistochemistry (IHC), and single‐cell RNA sequencing (scRNA‐seq) to assess the clinical relevance of purine metabolism in CRC. Low expression levels of five purine metabolism‐related genes—ADSL, APRT, ADCY3, NME3, and NME6—were associated with worse prognosis in CRC patient subgroups, including wild‐type TP53, mutant TP53, and microsatellite‐stable phenotypes. IHC‐based validation showed that NME3 expression was an independent prognostic factor, whereas ADSL and NME6 expressions were associated with clinical variables in prediction of prognosis. Notably, NME3 expression predicted a high risk in patients with early‐stage CRC, while ADSL and NME6 expressions were predictive in late‐stage CRC. scRNA‐seq analysis showed that four genes, excluding NME6, had low expression levels in epithelial cells at the late‐stage CRC. Despite the reversible nature of purine metabolism reactions, we demonstrated a consistent directional expression of these five prognostic purine metabolism‐related proteins in CRC tissues. We suggest that alterations in purine metabolism could serve as a clinically useful prognostic marker in CRC.